Evaluation of acute and sub-acute toxicity of Curcuma aeruginosa Roxb. essential oil in Sprague Dawley rats - Irmanida Batubara; Indah Fajarwati; Yessie Widya Sari; Gilles J. Guillemin; Innes Maulidya; Dinda Iryawati; Wulan Tri Wahyuni (Research in Pharmaceutical Sciences)
Background and purpose: Curcuma aeruginosa rhizome essential oil (CREO) is widely used in traditional medicine owing to its diverse biological activities. However, no information regarding its potential toxicity is available. This study aimed to evaluate the potential acute and sub-acute oral toxicities of CREO in Sprague Dawley rats. Experimental approach: CREO was isolated via steam distillation and characterized using GC/MS. For acute toxicity, rats were divided into four groups and administered CREO at 2, 4, 8, and 16 g/kg. For the sub-acute evaluation, 30 male and 30 female rats were divided into 6 groups (1 control, 3 treatment doses, and 2 satellite), with doses of 50, 100, and 200 mg/kg BW administered for 28 days. Findings/Results: GC/MS analysis identified eucalyptol, camphor, and epicurzerenone as the main phytochemically active components in CREO. The acute toxicity test demonstrated that CREO was toxic only at very high doses, with a lethal dose (LD50) of 5662 mg/kg of body weight. Evaluation of sub-acute toxicity showed no significant changes in body weight, hematological, biochemical, and histopathological parameters in rats receiving CREO at doses < 200 mg/kg. However, rats that received CREO at 200 mg/kg showed liver early abnormalities. Similar to most natural extracts, CREO showed a hormetic dose response. Conclusion and implications: This study suggests that CREO can be safely administered orally for therapeutic purposes at controlled doses. However, prolonged consumption and/or high doses may pose potential risks. Further evaluations are required to determine possible long-term effects.